1992
DOI: 10.7547/87507315-82-3-140
|View full text |Cite
|
Sign up to set email alerts
|

Aloe vera and the inflamed synovial pouch model

Abstract: Administration of air under the skin produced a pouch wall that closely resembled a synovium in that the inner lining was made up of macrophages and fibroblasts. Administration of 1% carrageenan directly into the 7-day-old air pouch produced an inflammation characterized by an increased number of mast cells in pouch fluid as well as an increase in wall vascularity. A punch biopsy weight of the pouch wall did not reveal an increase in 1% carrageenan-treated animals. However, a 10% Aloe vera treatment of carrage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…In addition, it was reported that AV stimulated blood vessel formation in the vascular chorioallantoic membrane in chicken by a glycoprotein which could promote the stimulation of endothelial cells proliferation in vitro and induced them to interact with collagen [48]. However, other studies postulated that AV reduced both the vascularity and mast cells number of inflamed synovial membrane to about the half [49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that AV stimulated blood vessel formation in the vascular chorioallantoic membrane in chicken by a glycoprotein which could promote the stimulation of endothelial cells proliferation in vitro and induced them to interact with collagen [48]. However, other studies postulated that AV reduced both the vascularity and mast cells number of inflamed synovial membrane to about the half [49].…”
Section: Discussionmentioning
confidence: 99%
“…The pulp, also called mucilaginous gel, has been used for therapeutic purposes due to the rich concentration of polysaccharides (Ni et al, 2004). The scientific interest in identifying the biological activity of these components that are mainly extracted and described in A. vera is because many studies have demonstrated their effectiveness in the treatment of diabetes (Okyar et al, 2001;Bolkent et al, 2004;Huseini et al, 2012), cholesterol (Lim et al, 2003;Huseini et al, 2012), cancer (Saini et al, 2010;Tomasin and Gomes-Marcondes, 2011), ulcers (Eamlamnam et al, 2006;Park et al, 2011), arthritis (Davis et al, 1992), dermatitis (West and Zhu, 2003;Kim et al, 2010) and inflammation (Eamlamnam et al, 2006;Prabjone et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…A. barbadensis Miller) belonging to the family Liliaceae has been known traditionally as the ''healing plant'' and used in a variety of cosmetic product formulations. The mucilaginous gel of this plant has been shown to have wound healing [8], anti-inflammation [9], immunostimulatory [10,11], and antioxidant properties [12]. However, in spite of its use as an ingredient in myriad health and cosmetic products the UV opacity potential of aloe gel has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 98%